Therapeutic effects of favipiravir against severe fever with thrombocytopenia syndrome virus infection in a lethal mouse model: Dose-efficacy studies upon oral administration - Tani, Hideki; Komeno, Takashi; Fukuma, Aiko; Fukushi, Shuetsu; Taniguchi, Satoshi; Shimojima, Masayuki; Uda, Akihiko; Morikawa, Shigeru; Nakajima, Nozomi; Furuta, Yousuke; Saijo, Masayuki (PloS one, 2018)
Severe fever with thrombocytopenia syndrome (SFTS), caused by SFTS virus (SFTSV), is a viral hemorrhagic fever with a high case fatality rate. Favipiravir was reported to be effective in the treatment of SFTSV infection in vivo in type I interferon receptor knockout (IFNAR-/-) mice at treatment dosages of both 60 mg/kg/day and 300 mg/kg/day for a duration of 5 days. In this study, the efficacy of favipiravir at dosages of 120 mg/kg/day and 200 mg/kg/day against SFTSV infection in an IFNAR-/- mouse infection model was investigated. IFNAR-/- mice were subcutaneously infected with SFTSV at a 1.0 × 10(6) 50% tissue culture infectious dose followed by twice daily administration of favipiravir, comprising a total dose of either 120 mg/kg/day or 200 mg/kg/day. The treatment was initiated either immediately post infection or at predesignated time points post infection. Neutralizing antibodies in the convalescent-phase mouse sera was examined by the pseudotyped VSV system. All mice treated with favipiravir at dosages of 120 mg/kg/day or 200 mg/kg/day survived when the treatment was initiated at no later than 4 days post infection. A decrease in body weight of mice was observed when the treatment was initiated at 3-4 days post infection. Furthermore, all control mice died. The body weight of mice did not decrease when treatment with favipiravir was initiated immediately post infection at dosages of 120 mg/kg/day and 200 mg/kg/day. Neutralizing antibodies were detected in the convalescent-phase mouse sera. Similar to the literature-reported peritoneal administration of favipiravir at 300 mg/kg/day, the oral administration of favipiravir at dosages of 120 mg/kg/day and 200 mg/kg/day to IFNAR-/- mice infected with SFTSV was effective.